A bibliometric analysis of metabolic dysfunction-associated steatotic liver disease in children from 2004 to 2024 - Xiaowei Gong; Xiaowei Gong; Siyu Bai; Enze Lei; Tao Lu; Yao Chen; Yao Chen; Yao Chen; Jianxin Cai; Jianzhong Liu; Jianzhong Liu; Jianzhong Liu; et al. (Frontiers in Pediatrics)
BackgroundMetabolic dysfunction-associated steatotic liver disease (MASLD), once known as Non-alcoholic fatty liver disease, impacts between 3% and 10% of children and adolescents globally, as well as nearly one-third of obsessed boys and one-quarter of obsessed girls, and is the most frequent cause of pediatric liver disease associated with the obesity epidemic. With the growing attention and increasing volume of literature on pediatric MASLD, there is an urgent need for bibliometric analysis and visualization in the area of pediatric MASLD study in terms of dissecting study priorities.MethodsLiterature was searched in the Web of Science Core Collection database, followed by categorization, bibliometric study as well as visual analysis conducted by applying software including Citespace, VOSviewer, and the R language. The study concentrated on analyzing information related to key authors, spatial and temporal distribution, core keywords, and important citations.ResultsIn total, 3,409 publications on pediatric MASLD were collected in the study, including 2,697 articles and 712 review articles. Between 2004 and 2024, the volume of publications had been constantly increasing per year. The country with the most numerous publications was the United States, which had extensive exchanges and collaborations with Italy, China, and England, followed by Italy. The Journal of Pediatric Gastroenterology and Nutrition had the greatest quantity of publications in this domain. The core literature was a clinical guideline. Insulin resistance, metabolic syndrome, steatohepatitis, hepatocellular carcinoma, cardiovascular risk, diabetes risk, diagnostic accuracy, lifestyle intervention, gut microbiome, probiotics, and metabolic dysfunction-associated steatotic liver disease were also hot topics and frontier trends in pediatric MASLD studies.ConclusionThis research represents the inaugural application of bibliometric analysis to examine the developmental trajectory of pediatric MASLD studies over the past two decades, which reveals that the etiology, pathological changes of the liver, relationship with obesity, complications, comorbidities, diagnosis and treatments of pediatric MASLD are the key focuses and provides academic references for pediatric clinicians and scholars to grasp the hotspots, the cutting edge and the evolving trends in the area.